The Agency for Healthcare Research and Quality (Italian Journal of Public Health, 2006)
The mission of the Agency for Healthcare Research and Quality is “to improve the quality, safety, efficiency,and effectiveness of health care for all Americans”. The organization and selected major activities of theAgency are briefly described.
Keywords: health services research; United States Agency for Healthcare Research and Quality